MINAT BELI ULANG DITINJAU DARI SIKAP, GAYA HIDUP DAN PERSEPSI KEBERMANFAATAN (STUDI KASUS KONSUMEN LUWES GENTAN) - Nursila Putri Nugraheni; Istiatin Istiatin; Sarsono Sarsono (ITB AAS INDONESIA Surakarta, 2020)
: The research aims to find out and describe the influence of simultaneously or partial attitude, life style and usefulness perception towards repurchase interest in Luwes Gentan Sukoharjo. This methodology research using quantitative descriptive research. The population was all consumer Luwes Gentan Sukoharjo unknown number. The number of samples was determined with the formula Lemeshow and the result 100 respondents. Sampling method using convenience sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis is multiple linier regression, F test, t test and determination coefficient. This test results the attitude, life style and usefulness perception simultaneously and significance effect on repurchase interest in Luwes Gentan Sukoharjo. Attitude influential positive and significance effect against the repurchase interest in Luwes Gentan Sukoharjo. Life style influential positive and significance effect against the repurchase interest in Luwes Gentan Sukoharjo. Usefulness perception influential positive and significance effect against the repurchase interest in Luwes Gentan Sukoharjo. Keywords : Repurchase Interest, Attitude, Life Style, Usefulness Perception